A tale of quantum jumps - Carmichael, Howard (New Zealand Science Review, 2015)
​In this year of light, our attention is quickly drawn to the many inroads into our day-to-day lives made, since the early 1960s, by the laser and the various technologies it has spawned: digital technologies (e.g. the optical fibre network), biomedical imaging and applications (e.g. in ophthalmology and dermatology), and applications in precision and ‘not-so-precision’ engineering – how did engineers ensure that the ends of the Chunnel would meet up in the middle? Likely only a very few of us are turned to a reflection on quantum mechanics by the year of light; but the rise of light, from its rather side-lined position in the late nineteenth century, as a well-understood Maxwell wave, to its position today as a diverse enabling technology, is very much a story of quantum mechanics, particularly in its early days, the days of the Old Quantum Theory where my tale of quantum jumps begins.